Evaluation of Interventions to Increase the Proportion of People Living with HIV Who Are Diagnosed, Initiated on, Adhering to and Retained in HIV Treatment and Care in South Africa : Formative Qualitative Research, Phase 1 Report - World Bank (World Bank, Washington, DC, 2016)
This report presents the findings of the first phase of a series of analytical and evaluation studies contributing to the design of an impact and process evaluation of South Africa’s National Adherence Guidelines for Chronic Diseases. The work package is a collaborative effort between the National Department of Health of South Africa, the National Health Laboratory Service (NHLS), the National Institute for Communicable Diseases (NICD), Boston University/Health Economics and Epidemiology Research Office (HE2RO) and the World Bank. The evaluation seeks to answer which mechanisms, strategies and delivery models work best in different settings in South Africa to improve enrolment in ART after HIV diagnosis, adherence to ART and long-term retention in care. The research was conducted in 2014 and consisted of a literature and data review and semi-structured interviews with key informants and health care clients in five selected provinces (Gauteng, KwaZulu-Natal, Limpopo, North West, and Western Cape). Based on the evidence, the report provides recommendations for future treatment adherence models and differentiated care in four priority areas: Improving clients’ understanding of their treatment; Providing focused counselling and grow accountability; Ensuring that there are tools and strategies to assist client self-monitoring; and Reducing barriers to diagnosis, treatment and care. This research contributed to the development of South Africa’s chronic treatment adherence guideline